2012
DOI: 10.1021/nn3008788
|View full text |Cite
|
Sign up to set email alerts
|

Bias-Stress Effect in 1,2-Ethanedithiol-Treated PbS Quantum Dot Field-Effect Transistors

Abstract: We investigate the bias-stress effect in field-effect transistors (FETs) consisting of 1,2-ethanedithiol-treated PbS quantum dot (QD) films as charge transport layers in a top-gated configuration. The FETs exhibit ambipolar operation with typical mobilities on the order of μ(e) = 8 × 10(-3) cm(2) V(-1) s(-1) in n-channel operation and μ(h) = 1 × 10(-3) cm(2) V(-1) s(-1) in p-channel operation. When the FET is turned on in n-channel or p-channel mode, the established drain-source current rapidly decreases from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
115
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(126 citation statements)
references
References 42 publications
10
115
1
Order By: Relevance
“…Moreover, previous measurements of the PbS QD FETs with different gate dielectric materials revealed that the transient current decay is independent of the choice of dielectric. 13 Therefore, our measured transient phenomena are due to the intrinsic properties of PbS QDs.…”
Section: Nano Lettersmentioning
confidence: 95%
See 1 more Smart Citation
“…Moreover, previous measurements of the PbS QD FETs with different gate dielectric materials revealed that the transient current decay is independent of the choice of dielectric. 13 Therefore, our measured transient phenomena are due to the intrinsic properties of PbS QDs.…”
Section: Nano Lettersmentioning
confidence: 95%
“…2,11 In FETs that operate under dark conditions, although it has been recently observed that certain deep defect states can actually assist carrier transport, 7,12 QD films still suffer from significant hysteresis effects where the source-drain current decays substantially in the scale of seconds after charge injection. 13 These effects were found to be independent of the gate dielectric and were thus attributed to the intrinsic properties of PbS QDs. However, no quantitative information on carrier density was presented, and the carrier trapping mechanism is still unresolved.…”
mentioning
confidence: 94%
“…43,44 The transients are also thermally activated (Supporting Information Figures S5 and S6). Activated I D transients in PbX QD FETs have been observed by others and attributed to a barrier to trapping, 42 thermally activated ligand rearrangements, 43 or QD motion. Below ∼150 K, the transients were greatly suppressed for FETs without ALD and often completely eliminated for infilled FETs.…”
mentioning
confidence: 99%
“…Thus, proper balancing of the charge carrier concentrations (mobilities) is necessary. The commonly used thiols mostly result in p-type materials [63,121], while hydrazine [66] and halides [122] were shown to be n-type dopants.…”
Section: The Role Of Surface Chemistrymentioning
confidence: 99%
“…On the other hand, oxygen/water can be adsorbed on the QD surface causing serious electron trapping [124]. Thiol crosslinkers are shown to passivate the surface against oxidation [69], nevertheless the transport in these samples is still limited by the electron trapping, and not by the hole current [121]. When halogenides are introduced to the latter stages of synthesis, they can fill vacancies on the QD surface, showing a similar passivation effect [113,125].…”
Section: The Role Of Surface Chemistrymentioning
confidence: 99%